Differences in Knowledge, Attitude, and Practice of The Community Parrots in Ternate and Sofifi, North Maluku - Ramadani, Annisa; Setia, Tatang Mitra; Mangunjaya, Fachruddin M.; Siregar, Benny A.; Basalamah, Fitriah (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
Abstract The community's habit of owning wild animals is still ongoing until now. This has become one of the threats to the existence of wildlife in their natural habitat. Parrots, with their ability to imitate surrounding sounds, have become a popular pet choice. Therefore, the purpose of this study is to determine the influence of knowledge, attitudes, and practices about parrots on the profile of the community. The study differentiates between those who owner bird and those who do not. Data collection was conducted for two months in Ternate and Sofifi, North Maluku. The method used was purposive sampling, interviewing as many as 104 respondents who had been determined. The interview data was processed into multiple linear regression values and canonical correlations. The results of this research identified that the majority of those who owned parrots were aged between 42–57 (36%); female (52%); with high school graduates (46%); and engaged in various professions, such as housewives or entrepreneurs (71%). On the other hand, those who were non-owner parrots were dominated by individuals aged 10–25 (46%); male (65%); with undergraduate degrees (62%); and categorized as students (38%). The results of this study show that knowledge and attitudes have an influence on education, profession, and age of the community on the topic of curly-billed bird maintenance. Abstrak Kebiasaan masyarakat memiliki satwa liar masih berlangsung hingga sekarang. Hal ini menjadi salah satu ancaman terhadap keberadaan satwa liar di habitat aslinya. Burung paruh bengkok memiliki kemampuan meniru suara di sekitarnya, dan menjadi satwa liar yang populer sebagai peliharaan. Oleh karena itu, tujuan penelitian ini adalah untuk mengetahui pengaruh pengetahuan, sikap, dan kesadaran tentang pemeliharaan burung paruh bengkok terhadap profil masyarakat. Studi ini membedakan, antara masyarakat yang memelihara burung dan yang tidak. Pengumpulan data dilakukan selama dua bulan di Kota Ternate dan Sofifi, Maluku Utara. Metode yang digunakan purposive sampling, mewawancarai sebanyak 104 responden yang telah ditentukan. Data wawancara tersebut diolah menggunakan software SPSS 22.0 untuk memperoleh nilai regresi linier berganda dan kolerasi kanonikal. Hasil penelitian, mengidentifikasi bahwa mayoritas dari mereka yang memiliki burung paruh bengkok berusia antara 42–57 (36%); berjenis kelamin perempuan (52%); tingkat pendidikan SMA (46%); dan memiliki profesi lainnya, seperti ibu rumah tangga atau pengusaha (71%). Di sisi lain, masyarakat yang tidak memelihara burung paruh bengkok, didominasi yang berusia 10–25 (46%); berjenis kelamin laki-laki (65%); tingkat pendidikan sarjana (62%); dan lebih ddidominasi oleh pelajar/mahasiswa (38%). Hasil penelitian ini menunjukkan bahwa pengetahuan dan sikap memiliki pengaruh dengan pendidikan, profesi, dan usia masyarakat terhadap topik pemeliharaan burung paruh bengkok.